2003
DOI: 10.1002/ana.10648
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glial glutamate transport in a mouse tuberous sclerosis epilepsy model

Abstract: Excessive astrocytosis in cortical tubers in tuberous sclerosis complex (TSC) suggests that astrocytes may be important for epileptogenesis in TSC. We previously demonstrated that astrocyte-specific Tsc1 gene inactivation in mice (Tsc1 cKO mice) results in progressive epilepsy. Here, we report that glutamate transporter expression and function is impaired in Tsc1 cKO astrocytes. Tsc1 cKO mice exhibit decreased GLT-1 and GLAST protein expression. Electrophysiological assays demonstrate a functional decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
146
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 175 publications
(156 citation statements)
references
References 20 publications
5
146
1
2
Order By: Relevance
“…101 In addition, GLT1 expression and glutamate transport are decreased in a mouse model of tuberous sclerosis epilepsy, a disease involving seizures and mental retardation. 102 In a seizuresusceptible mouse strain, GLT1 mRNA and protein were downregulated in the parietal cortex, whereas in the hippocampus there was a decrease in mRNA expression without a corresponding decrease in the protein level. 103 This observation was corroborated in another study of genetically epilepsy-prone animals showing decreased GLT1 RNA expression in the cortex, striatum, CA1 and the inferior colliculus, without a corresponding change in protein levels.…”
Section: Epilepsymentioning
confidence: 98%
“…101 In addition, GLT1 expression and glutamate transport are decreased in a mouse model of tuberous sclerosis epilepsy, a disease involving seizures and mental retardation. 102 In a seizuresusceptible mouse strain, GLT1 mRNA and protein were downregulated in the parietal cortex, whereas in the hippocampus there was a decrease in mRNA expression without a corresponding decrease in the protein level. 103 This observation was corroborated in another study of genetically epilepsy-prone animals showing decreased GLT1 RNA expression in the cortex, striatum, CA1 and the inferior colliculus, without a corresponding change in protein levels.…”
Section: Epilepsymentioning
confidence: 98%
“…Pharmacological inhibition of EAAT2 reduced the threshold for evoking epileptiform activity (Campbell and Hablitz, 2004; Demarque et al, 2004). Reduced expression of EAAT2 and glutamate‐aspartate transporters (GLAST, SLC1A3) also occurs in a tuberous sclerosis epilepsy model (Wong et al, 2003). However, the studies investigating the functional expression of astrocytic glutamate transporters in human epilepsy are inconsistent.…”
Section: Astrocytes In the Diseased Brain Are Central To Neuropathologymentioning
confidence: 99%
“…Nrf2‐regulated genes are preferentially activated in astrocytes, boosting their detoxification and antioxidant functions (Vargas and Johnson, 2009). Activation of Nrf2 in astrocytes protects dopaminergic neurons from oxidative stress (Miyazaki et al, 2011; Wong et al, 2003). Protein S100ß is expressed in various cell types with the highest level in the cytoplasm of astrocytes (Selinfreund, Barger, Pledger, & Vaneldik, 1991) which release it into the extracellular space.…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%
“…Furthermore, inactivation of the astrocyte glutamate transporters, GLT-1 or GLAST, results in decreased seizure threshold or spontaneous seizures in mice (Tanaka et al, 1997;Watanabe et al, 1999). We have previously shown that astrocytes from Tsc1 GFAP CKO mice exhibit decreased expression and function of GLT-1 and GLAST (Wong et al, 2003), suggesting the possibility that abnormal glutamate homeostasis could also contribute to neuronal dysfunction in the Tsc1 GFAP CKO mice. Thus, in the present study, we examined the hypothesis that Tsc1 GFAP CKO mice have elevated extracellular glutamate levels, which may contribute to excitotoxic neuronal death, abnormal glutamatergic synaptic physiology, and impaired behavioral conditioning and learning.…”
Section: Introductionmentioning
confidence: 99%